Examining Multicultural Representation in Lepus Songket of Palembang - Hutadjulu, Dicky Maryoga (Jurnal Dinamika Sosial Budaya, 2022)
Sriwijaya in the 7th  century well known as Svarnadwipa that means island of gold. The Richness of gold made the kingdom produce woven fabric with golden thread called, songket.                          Lepus Songket is the ultimate songket in Palembang. Lepus has meaning covering , all the gold threads covered the whole fabrics.                          This article explains about the multicultural representation of Lepus Palembang songket. The examination of multicultural that influenced Lepus Songket would be presented. Lepus history is interesting, since the origin of it came from royalty family.  The conclusion of this article suggest Lepus songket of Palembang is the precious multicultural legacy. The young generation should be the preserver of Lepus.
Keywords: Keywords; Lepus; Palembang Songket; Sriwijaya; Multicultural